ANALISIS RETRIBUSI PASAR DAN KONTRIBUSINYA DALAM PENDAPATAN ASLI DAERAH KABUPATEN ENDE - Wende, Tilza Juliza S A; Londa, Yulita; Kapa, Sesilianus (Jurnal Riset Ilmu Akuntansi, 2020)
The purpose of this study is to analyze the level of contribution and effectiveness of market retribution on the local revenue of Ende Regency in the Regional Revenue Agency of Ende Regency from 2015-2017. The data analysis used is quantitative descriptive analysis, by calculating and explaining the level of contribution and effectiveness of market fees to the local revenue of Ende district. As for the population in this study is the target data and the realization of Market Levies and Local Revenue in Ende Regency. This study uses a sample, namely the target data and the realization of Market Levies and Local Revenue in Ende Regency 2015-2017. The results of this study are for the contribution of market retribution to the local revenue of Ende Regency in 2015-2017, it can be concluded that the results are still below 2% or still very less in accordance with the contribution criteria table. This criterion refers to the Decree of the Minister of Home Affairs No. 690,900-327 of 1996 which stipulates that if the percentage yield is 0.00% - 10%, the category is very poor. Whereas for the level of effectiveness of the market levies of Ende Regency in 20152016 it is categorized as very effective, while in 2017 it is categorized as less effective, this refers to the Decree of the Minister of Home Affairs No.690,900-327 of 1996 which regulates that if the percentage is> 100% it is categorized as very effective. , meanwhile, if the percentage is> 60% - 80% it is categorized as less effective.